Pengalaman pasien dengan tuberkulosis multi-drug resistant (TB- MDR) - Hastuti, Sastri; Abdullah, Asnawi; Marthoenis, Marthoenis; Maidar, Maidar; Zakaria, Radhiah (Holistik Jurnal Kesehatan, 2025)
Background: Multidrug-resistant tuberculosis (MDR-TB) not only impacts physical health but also triggers psychological disorders due to the lengthy treatment process, social stigma, and limited mental health support services. This puts patients at high risk for anxiety, stress, and depression. Purpose: To explore the experiences of patients with multi-drug resistant tuberculosis (MDR-TB). Method: A qualitative design with a phenomenological approach. Data were obtained through in-depth interviews with seven MDR-TB patients, three family members, and two healthcare workers in Bireuen Regency, Aceh. Data analysis used Huberman's model, including reduction, presentation, and conclusion drawing with source triangulation. Results: The study identified five main themes: stressors, mental health conditions, coping strategies, family perspectives, and healthcare professionals' perceptions. Patients experienced anxiety, uncertainty about recovery, social stigma, economic constraints, and severe medication side effects. Family support, religious approaches, and adequate information proved crucial in helping patients cope with psychological distress. Conclusion: MDR-TB patients face significant mental burdens, while psychosocial support services in healthcare facilities remain limited. Strengthening education, family support, and integrating mental health services are needed to improve the quality of life and treatment adherence of MDR-TB patients.   Keywords: Coping Strategies; Family Support; Mental Health; Multidrug-Resistant Tuberculosis (MDR-TB); Social Stigma.   Pendahuluan: Tuberkulosis Multi-Drug Resistant (TB-MDR) tidak hanya berdampak pada kesehatan fisik, tetapi juga memicu gangguan psikologis akibat proses pengobatan yang panjang, stigma sosial, serta keterbatasan layanan pendampingan mental. Kondisi ini menempatkan pasien pada risiko tinggi mengalami kecemasan, stres, dan depresi. Tujuan: Untuk mengeksplorasi pengalaman pasien dengan tuberkulosis multi-drug resistant (TB- MDR). Metode: Desain kualitatif dengan pendekatan fenomenologi. Data diperoleh melalui wawancara mendalam terhadap tujuh pasien TB-MDR, tiga anggota keluarga, dan dua tenaga kesehatan di Kabupaten Bireuen, Aceh. Analisis data menggunakan model Huberman meliputi reduksi, penyajian, dan penarikan kesimpulan dengan triangulasi sumber. Hasil: Ditemukan lima tema utama, yaitu faktor penyebab stres, kondisi kesehatan mental, strategi koping, pandangan keluarga, serta persepsi tenaga kesehatan. Pasien mengalami kecemasan, ketidakpastian kesembuhan, stigma sosial, keterbatasan ekonomi, serta efek samping obat yang berat. Dukungan keluarga, pendekatan religius, dan informasi yang memadai terbukti berperan penting dalam membantu pasien mengatasi tekanan psikologis. Simpulan: Pasien TB resisten multidrug (TB-MDR) menghadapi beban mental yang signifikan, sementara layanan dukungan psikososial di fasilitas kesehatan masih terbatas. Penguatan pendidikan, dukungan keluarga, dan integrasi layanan kesehatan mental diperlukan untuk meningkatkan kualitas hidup dan kepatuhan pengobatan pasien TB-MDR.   Kata Kunci: Dukungan Keluarga; Kesehatan Mental; Multidrug-Resistant Tuberculosis (TB-MDR); Stigma Sosial; Strategi Koping.